Implementasi MSIP (Manajemen Sistem Informasi Pendistribusian) Keluar Masuk Obat Pada Gudang Farmasi Kelapa - Sarwindah Sarwindah; Marini Marini; Tirta Aditya Pratama (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
The process of drug distribution is one of the main processes in drug management which has an important role in managing drug availability. In its implementation, the drug distribution process requires information regarding the receipt, supply and expenditure of the drug between the sending and receiving parties, where the information can be changed periodically according to the entry and exit of the drug. Therefore Pharmacy Pharmacy warehouse in Kelapa Puskesmas which has the task of distributing drugs to sub-service units should be able to meet the needs in managing information on the drug distribution process. This research was conducted to analyze and design "Web-Based Drug Distribution Information System in Coconut Pharmacy Warehouse". In this research, the research method used by the author is the Oriented Object method with case studies in the distribution of drugs and to design information systems using the Oriented object approach and for the development method using the UML method.it can be seen that the Drug Distribution Information System in the Web-Based Coconut Pharmacy Warehouse is currently experiencing problems, because there are some data processing processes that are still conventional in nature, and there is still no integration of drug inventory data with drug sales data and so forth